Методичні засади вивчення антропогенного впливу на формуванні якості поверхневих вод - Мольчак, Ярослав Олександрович; Фесюк, Василь Олександрович; Панькевич, Сергій Григорович; Molchak, Yaroslav O.; Fesiuk, Vasyl O.; Pankevych, Serhii H. (Державне агентство водних ресурсів України, 2011)
Methodical bases of study of anthropogenic influencing on forming of quality of superficial waters In the article there is the question about the methodical bases of research of quality of water, methods of analysis of spatio-temporal conformities to the law of the high-quality state of waters, estimation of influencing of economic activity on quality of superficial waters
Methodical bases of study of anthropogenic influencing on forming of quality of superficial waters
Keywords: methodical bases of research of quality of water; spatio-temporal conformities to the law of the high-quality state of waters; influence of economic activity on quality of superficial waters